Use of Repetitive Transcranial Magnetic Stimulation in Treatment of Negative Symptoms of Schizophrenia - Gokben Hızlı Sayar; Huseyin Bulut; Nevzat Tarhan (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2015)
In this review, we explore the evidence concerning the efficacy of repetitive transcranial magnetic stimulation (rTMS) to treat negative symptoms of schizophrenia. The majority of protocols have utilized high-frequency excitatory rTMS over the left dorsolateral prefrontal cortex (DLPFC) with limited therapeutic benefits in ameliorating negative symptoms. Although there are many promising results, current evidence does not fully support the clinical use of rTMS in the treatment of negative symptoms or cognitive dysfunction in patients with schizophrenia. Due to the disabling nature of these symptoms, clinical use of this technique could be justified in certain cases although overall response rates are not likely to be high. Treatment of cognitive dysfunction with rTMS is a promising but new area of research. Regarding side effects, the active rTMS intervention was well tolerated. Future research must focus on the clinical efficacy of patterned rTMS (e.g., theta burst stimulation), and optimum stimulation site and parameters.